Method for preparing antibacterial glaze from zirconium silicate
By using erbium-doped zirconium silicate and silver bismuth in the antibacterial glaze to modify the composite titanium dioxide, combined with a composite dispersant compounded by modified acrylic acid and polyethylene glycol, the problem of reducing the antibacterial effect of existing antibacterial glaze during high temperature sintering and difficult to clean the glaze surface is solved, and the glaze surface self-cleaning and efficient antibacterial effect is achieved.
Patent Information
- Application Number
- CN202311732257.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-16
- Publication Date
- 2025-06-17
AI Technical Summary
The antibacterial effect of existing antibacterial glazes is reduced during high temperature sintering, and the glaze surface is easily contaminated with dirt and difficult to clean.
Erbium-doped zirconium silicate and silver bismuth modified composite titanium dioxide are used as antibacterial components, and a composite dispersant compounded with modified acrylic acid and polyethylene glycol is added during the preparation process. Through wet ultrafine grinding technology, the material ratio is controlled to improve the self-cleaning performance of the glaze surface.
Maintain a high antibacterial effect after high temperature sintering. The glaze surface has self-cleaning properties, can effectively remove pollutants such as formaldehyde and improve the practicality of antibacterial glaze.
Smart Images

Figure BDA0004610707760000081
Abstract
Description
Technical Field
[0001] The present invention relates to the field of glazes, and specifically to a method for preparing antibacterial glazes using zirconium silicate. Background Art
[0002] With the progress of society, people's health awareness is constantly increasing, so more and more attention is paid to the field of antibacterial materials. Ceramic products are widely used in daily life, so the application of antibacterial glazes in industries such as construction, water treatment, and medical and health has received more and more attention.
[0003] Existing antibacterial glazes mostly add rare earth metals to achieve antibacterial effects. However, some rare earth metal elements are low-temperature materials, which will reduce the antibacterial effect during high-temperature sintering, and at the same time cause an increase in the glass phase and a decrease in the crystal phase in the glaze, thereby reducing the wear resistance. At the same time, there are a large number of fine pinholes and pits on the surface of the glaze formed by the existing antibacterial glazes on the market, which are easy to stain with dirt and difficult to clean. Summary of the Invention
[0004] The purpose of the present invention is to provide a method for preparing antibacterial glazes using zirconium silicate to solve the problems in the prior art.
[0005] To solve the above technical problems, the present invention provides the following technical solutions:
[0006] A method for preparing antibacterial glazes using zirconium silicate, comprising the following steps:
[0007] S1: Mix erbium-doped zirconium silicate, silver-bismuth modified composite titanium dioxide, and base glaze to obtain a base glaze;
[0008] S2: Add a composite dispersant prepared by compounding modified acrylic acid and polyethylene glycol to the base glaze, perform wet ultrafine grinding, wash and dry to obtain an antibacterial glaze prepared using zirconium silicate.
[0009] Further, the preparation of erbium-doped zirconium silicate includes the following steps: Mix zirconium oxychloride octahydrate and deionized water, add erbium nitrate, and adjust the pH to 2.8 - 3.2 with ammonia water, denoted as solution A; Mix sodium silicate and deionized water, and adjust the pH to 2.8 - 3.2 with hydrochloric acid, denoted as solution B; Under stirring conditions, add solution A and solution B to ammonium fluoride solution together, adjust the pH to 2.8 - 3.2 with hydrochloric acid, keep the temperature at 75 - 80 °C in a water bath for 5 - 6 h, cool and age for 10 - 12 h, filter and wash 3 - 5 times with deionized water and ethanol, dry, add sodium fluoride and sodium chloride, mix and pass through a 200-mesh sieve, keep the temperature at 900 °C for 2 h, cool and grind, and perform pickling, washing, and drying in sequence to obtain erbium-doped zirconium silicate.
[0010] Further, the preparation of silver-bismuth modified composite titanium dioxide includes the following steps: Mix anhydrous ethanol and tetrabutyl titanate, add a mixed solution of deionized water, anhydrous ethanol, and cerium nitrate, then sequentially add bismuth nitrate and silver nitrate, transfer to a reaction kettle, keep warm at 105 - 110 °C for 46 - 48 h, wash centrifugally with anhydrous ethanol and deionized water 3 - 5 times in sequence, dry, heat up to 200 °C at a rate of 15 °C / min in an argon atmosphere and keep warm for 1 h, then heat up to 450 °C at the same rate and keep warm for 2 h to obtain silver-bismuth modified composite titanium dioxide.
[0011] Further, the mass ratio of bismuth nitrate, silver nitrate, and cerium nitrate is 0.1:0.1:0.29.
[0012] Further, by mass fraction, the composition of the base glaze is: 10 - 20% erbium-doped zirconium silicate, 8 - 16% silver-bismuth modified composite titanium dioxide, and the balance is the base glaze.
[0013] Further, by mass parts, the composition of the base glaze is: 19 - 20 parts of potassium feldspar, 5 - 6 parts of sodium feldspar, 31 - 33 parts of silica powder, 2 - 4 parts of zinc oxide, 3 - 6 parts of calcite, 3 - 5 parts of dolomite, 15 - 17 parts of wollastonite, 2 - 3 parts of barium carbonate, and 3 - 5 parts of 809 frit.
[0014] Further, the mass ratio of modified acrylic acid to polyethylene glycol in the composite dispersant is 1:10.
[0015] Further, the working conditions of wet ultrafine grinding are: Grind with a medium stirring mill, the rotational speed of the main shaft of the medium stirring mill is 2000 rpm, the grinding medium used is yttrium-stabilized zirconia beads with a bead diameter of 0.2 - 0.3 mm, the volume filling rate of the grinding beads is 78 vol.%, the pH is 6.8 - 7.2, and the grinding time is 80 - 100 min.
[0016] Further, the mass ratio of the composite dispersant to the base glaze is 2.2 - 2.8%.
[0017] Further, the preparation of modified acrylic acid includes the following steps:
[0018] Mix acrylic acid, itaconic acid, 2-acrylamido-2-methylpropanesulfonic acid, sodium hypophosphite, and deionized water, heat up to 65 - 70 °C, under nitrogen protection, add an aqueous solution of ammonium persulfate, heat up to 75 - 80 °C, and then adjust the pH to 7 - 8 with sodium hydroxide to obtain modified acrylic acid.
[0019] The beneficial effects of the present invention:
[0020] The present invention provides a method for preparing an antibacterial glaze using zirconium silicate. Rare earth ions with high temperature resistance are introduced into the glaze to enhance its antibacterial property, so that it still maintains a high antibacterial effect after high temperature sintering. By proportioning the glaze components and introducing a composite dispersant during the preparation of the glaze for wet ultra-fine grinding, and by controlling the material ratio, the glaze surface formed by the prepared antibacterial glaze has the functions of self-cleaning and formaldehyde removal, etc., greatly improving the practicality of the antibacterial glaze and facilitating its market promotion.
[0021] In the present invention, the potassium and sodium contents are adjusted in the base glaze to ensure that the viscosity of the glaze melt is moderate. By controlling the content of silicon dioxide in the antibacterial glaze, the glaze can spread smoothly on the surface of the green body, reducing the pits on the glaze surface. Dolomite is used to replace calcite to adjust the high temperature viscosity and surface tension of the glaze. Adding a small amount of zinc helps to improve the elastic properties of the glaze surface. The introduction of wollastonite is beneficial to reducing the bubbles on the glaze surface and improving the smoothness of the glaze surface formed after sintering of the glaze.
[0022] In the present invention, zirconium silicate has excellent physical and chemical properties such as high temperature resistance and strong acid and alkali corrosion resistance as an antibacterial glaze. However, large particle size and serious agglomeration will affect the effectiveness of its use as an antibacterial glaze. In the present invention, a nano-scale erbium-doped zirconium silicate with a narrow particle size distribution and no agglomeration is synthesized, thereby greatly improving its dispersion uniformity in the antibacterial glaze.
[0023] A photocatalytic antibacterial material titanium dioxide with excellent broad-spectrum antibacterial efficacy is introduced into the antibacterial glaze. However, pure titanium dioxide will reduce its antibacterial property when sintered at a temperature higher than 800 °C. Therefore, in the present invention, a silver-bismuth modified composite titanium dioxide is synthesized to enhance its high temperature resistance. And when preparing the composite titanium dioxide, argon atmosphere is used for sintering, so that it still maintains excellent antibacterial performance after high temperature sintering. Compared with titanium dioxide, the silver-bismuth modified composite titanium dioxide greatly improves its photocatalytic degradation efficiency after being polluted by organic pollutants, thereby enhancing the self-cleaning performance of the glaze surface formed by the glaze.
[0024] During wet ultra-fine grinding, when adding a composite dispersant composed of 2.2-2.8% of modified acrylic acid and polyethylene glycol, the base glaze is ultra-finely ground to obtain particles with finer particle size and narrower particle size distribution. The composite dispersant generates more effective hydrogen bonds, making it easy to adsorb on the particle surface and wet. During the grinding process, it can effectively improve the rheological properties, making the particles generate strong electrostatic repulsion potential energy and steric hindrance potential energy, which helps the particles to break and makes their particle sizes tend to be consistent, making the glaze surface formed after sintering dense, thereby greatly enhancing its self-cleaning property. Specific embodiments
[0025] The technical solutions of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments. All other embodiments obtained by those of ordinary skill in the art based on the embodiments of the present invention without creative efforts belong to the scope of protection of the present invention.
[0026] In addition, the technical solutions between various embodiments can be combined with each other, but it must be based on the ability of those of ordinary skill in the art to implement. When the combination of technical solutions is contradictory or cannot be implemented, it should be considered that such a combination of technical solutions does not exist and is not within the scope of protection required by the present invention.
[0027] The technical solutions of the present invention will be further described in detail below in conjunction with specific embodiments. It should be understood that the following embodiments are only used to explain the present invention and are not used to limit the present invention.
[0028] Embodiment 1: A method for preparing an antibacterial glaze using zirconium silicate, comprising the following steps:
[0029] S1: Mix erbium-doped zirconium silicate, silver-bismuth modified composite titanium dioxide, and a base glaze to obtain a base glaze;
[0030] By mass fraction, the composition of the base glaze is: 10% erbium-doped zirconium silicate, 8% silver-bismuth modified composite titanium dioxide, and the balance is the base glaze;
[0031] The preparation of erbium-doped zirconium silicate includes the following steps: Mix 16.11 g of zirconium oxychloride octahydrate and 60 mL of deionized water, add 1 g of erbium nitrate, and adjust the pH to 2.8 with ammonia water, denoted as solution A; Mix 17.04 g of sodium silicate and 30 mL of deionized water, and adjust the pH to 2.8 with hydrochloric acid, denoted as solution B; Under stirring conditions, add the prepared solutions A and B together to 50 mL of a 2 mol / L ammonium fluoride solution, adjust the pH to 2.8 with hydrochloric acid, keep the temperature at 75 °C in a water bath for 6 h, cool and age for 10 h, filter and wash 3 times with deionized water and ethanol, dry, add 5 wt% sodium fluoride and 10 wt% sodium chloride, mix and pass through a 200-mesh sieve, keep the temperature at 900 °C for 2 h, cool and grind, and perform pickling, water washing, and drying in sequence to obtain erbium-doped zirconium silicate;
[0032] The preparation of silver-bismuth modified composite titanium dioxide includes the following steps: Mix 15 mL of absolute ethanol and 5 mL of tetrabutyl titanate, add a mixture of 5 mL of deionized water, 15 mL of absolute ethanol, and 0.29 g of cerium nitrate, then successively add 0.1 g of bismuth nitrate and 0.1 g of silver nitrate. Transfer to a reaction kettle and keep it at 110 °C for 46 h. Centrifuge and wash with absolute ethanol and deionized water three times in sequence, dry, heat to 200 °C at a rate of 15 °C / min under an argon atmosphere and keep it for 1 h, then heat to 450 °C at the same rate and keep it for 2 h to obtain silver-bismuth modified composite titanium dioxide;
[0033] By mass fraction, the composition of the base glaze is: 19 parts of potassium feldspar, 5 parts of sodium feldspar, 31 parts of silica powder, 2 parts of zinc oxide, 3 parts of calcite, 3 parts of dolomite, 15 parts of wollastonite, 2 parts of barium carbonate, and 3 parts of 809 frit;
[0034] The mass ratio of the composite dispersant to the base glaze is 2.2%;
[0035] The mass ratio of modified acrylic acid to polyethylene glycol in the composite dispersant is 1:10;
[0036] The preparation of modified acrylic acid includes the following steps: Mix 8 g of acrylic acid, 7.2 g of itaconic acid, 5.7 g of 2-acrylamido-2-methylpropanesulfonic acid, 7 g of sodium hypophosphite, and 26 mL of deionized water, heat to 65 °C, under nitrogen protection, add 5 mL of 20% ammonium persulfate aqueous solution, heat to 75 °C, and then adjust the pH to 7 with sodium hydroxide to obtain modified acrylic acid;
[0037] The working conditions of wet ultrafine grinding are: Grind with a medium stirring mill. The rotational speed of the main shaft of the medium stirring mill is 2000 rpm. The grinding medium used is yttrium-stabilized zirconia beads with a bead diameter of 0.2 mm. The volume filling rate of the grinding beads is 78 vol.%, the pH is 6.8, and the grinding time is 80 min;
[0038] S2: Add a composite dispersant prepared by compounding modified acrylic acid and polyethylene glycol to the base glaze, carry out wet ultrafine grinding, wash and dry to obtain an antibacterial glaze prepared using zirconium silicate.
[0039] Example 2: A method for preparing an antibacterial glaze using zirconium silicate, including the following steps:
[0040] S1: Mix erbium-doped zirconium silicate, silver-bismuth modified composite titanium dioxide, and the base glaze to obtain the base glaze;
[0041] By mass fraction, the composition of the base glaze is: 15% erbium-doped zirconium silicate, 12% silver-bismuth modified composite titanium dioxide, and the balance is the base glaze;
[0042] The preparation of erbium-doped zirconium silicate includes the following steps: Mix 16.11 g of zirconium oxychloride octahydrate with 60 mL of deionized water, add 1 g of erbium nitrate, and adjust the pH to 3 with ammonia water, denoted as solution A; Mix 17.04 g of sodium silicate with 30 mL of deionized water, and adjust the pH to 3 with hydrochloric acid, denoted as solution B; Under stirring conditions, add the prepared solutions A and B together to 50 mL of ammonium fluoride solution with a concentration of 2 mol / L, adjust the pH to 3 with hydrochloric acid, keep it in a water bath at 78 °C for 5.5 h, cool and age for 11 h, filter and wash 4 times with deionized water and ethanol, dry, add 5 wt% sodium fluoride and 10 wt% sodium chloride, mix and pass through a 200-mesh sieve, keep it at 900 °C for 2 h, cool and grind, and perform pickling, water washing, and drying in sequence to obtain erbium-doped zirconium silicate;
[0043] The preparation of silver-bismuth modified composite titanium dioxide includes the following steps: Mix 15 mL of anhydrous ethanol and 5 mL of tetrabutyl titanate, add a mixture of 5 mL of deionized water, 15 mL of anhydrous ethanol, and 0.29 g of cerium nitrate, then add 0.1 g of bismuth nitrate and 0.1 g of silver nitrate in sequence, transfer to a reaction kettle and keep it at 110 °C for 47 h, centrifuge and wash 4 times with anhydrous ethanol and deionized water in sequence, dry, heat to 200 °C at a rate of 15 °C / min in an argon atmosphere and keep it for 1 h, then heat to 450 °C at the same speed and keep it for 2 h to obtain silver-bismuth modified composite titanium dioxide;
[0044] By mass fraction, the composition of the base glaze is: 19.5 parts of potassium feldspar, 5.5 parts of sodium feldspar, 32 parts of silica powder, 3 parts of zinc oxide, 5 parts of calcite, 4 parts of dolomite, 16 parts of wollastonite, 2.5 parts of barium carbonate, and 4 parts of 809 frit;
[0045] The mass ratio of the composite dispersant to the base glaze is 2.6%;
[0046] The mass ratio of modified acrylic acid to polyethylene glycol in the composite dispersant is 1:10;
[0047] The preparation of modified acrylic acid includes the following steps: Mix 8 g of acrylic acid, 7.2 g of itaconic acid, 5.7 g of 2-acrylamido-2-methylpropanesulfonic acid, 7 g of sodium hypophosphite, and 26 mL of deionized water, heat to 68 °C, under nitrogen protection, add 5 mL of 20% ammonium persulfate aqueous solution, heat to 78 °C, and then adjust the pH to 7.5 with sodium hydroxide to obtain modified acrylic acid;
[0048] The working conditions of wet ultra-fine grinding are: Grind with a medium stirring mill, the rotation speed of the main shaft of the medium stirring mill is 2000 rpm, the grinding medium used is yttrium-stabilized zirconia beads with a bead diameter of 0.2 mm, the volume filling rate of the grinding beads is 78 vol.%, the pH is 7, and the grinding time is 90 min;
[0049] S2: Add a composite dispersant prepared by compounding modified acrylic acid and polyethylene glycol to the base glaze, conduct wet ultra-fine grinding, wash and then dry to obtain an antibacterial glaze prepared using zirconium silicate.
[0050] Example 3: A method for preparing an antibacterial glaze using zirconium silicate, comprising the following steps:
[0051] S1: Mix erbium-doped zirconium silicate, silver-bismuth modified composite titanium dioxide, and a base glaze to obtain a base glaze;
[0052] By mass fraction, the composition of the base glaze is: 20% erbium-doped zirconium silicate, 16% silver-bismuth modified composite titanium dioxide, and the balance is the base glaze;
[0053] The preparation of erbium-doped zirconium silicate includes the following steps: Mix 16.11 g of zirconium oxychloride octahydrate and 60 mL of deionized water, add 1 g of erbium nitrate, and adjust the pH to 3.2 with ammonia water, denoted as solution A; Mix 17.04 g of sodium silicate and 30 mL of deionized water, and adjust the pH to 3.2 with hydrochloric acid, denoted as solution B; Under stirring conditions, add the prepared solutions A and B together to 50 mL of ammonium fluoride solution with a concentration of 2 mol / L, adjust the pH to 3.2 with hydrochloric acid, keep the temperature at 80 °C in a water bath for 5 h, cool and age for 12 h, filter and wash 5 times with deionized water and ethanol, dry, add 5 wt% sodium fluoride and 10 wt% sodium chloride, mix and pass through a 200-mesh sieve, keep the temperature at 900 °C for 2 h, cool and grind, and conduct pickling and water washing in sequence, then dry to obtain erbium-doped zirconium silicate;
[0054] The preparation of silver-bismuth modified composite titanium dioxide includes the following steps: Mix 15 mL of anhydrous ethanol and 5 mL of tetrabutyl titanate, add a mixture of 5 mL of deionized water, 15 mL of anhydrous ethanol, and 0.29 g of cerium nitrate, then add 0.1 g of bismuth nitrate and 0.1 g of silver nitrate in sequence, transfer to a reaction kettle and keep the temperature at 110 °C for 48 h, centrifuge and wash 5 times with anhydrous ethanol and deionized water in sequence, dry, heat up to 200 °C at a rate of 15 °C / min in an argon atmosphere and keep the temperature for 1 h, then heat up to 450 °C at the same rate and keep the temperature for 2 h to obtain silver-bismuth modified composite titanium dioxide;
[0055] By mass parts, the composition of the base glaze is: 20 parts of potassium feldspar, 6 parts of sodium feldspar, 33 parts of silica powder, 4 parts of zinc oxide, 6 parts of calcite, 5 parts of dolomite, 17 parts of wollastonite, 3 parts of barium carbonate, and 5 parts of 809 frit;
[0056] The mass ratio of the composite dispersant to the base glaze is 2.8%;
[0057] The mass ratio of modified acrylic acid to polyethylene glycol in the composite dispersant is 1:10;
[0058] The preparation of modified acrylic acid includes the following steps: Mix 8 g of acrylic acid, 7.2 g of itaconic acid, 5.7 g of 2-acrylamido-2-methylpropanesulfonic acid, 7 g of sodium hypophosphite, and 26 mL of deionized water, heat up to 70 °C, under nitrogen protection, add 5 mL of 20% ammonium persulfate aqueous solution, heat up to 80 °C, and then adjust the pH to 8 with sodium hydroxide to obtain modified acrylic acid;
[0059] The working conditions for wet ultrafine grinding are as follows: Grind with a medium agitation mill. The rotational speed of the main shaft of the medium agitation mill is 2000 rpm. The grinding medium used is yttrium-stabilized zirconia beads with a bead diameter of 0.3 mm. The volume filling rate of the grinding beads is 78 vol.%, the pH is 7.2, and the grinding time is 100 min;
[0060] S2: Add a composite dispersant prepared by compounding modified acrylic acid and polyethylene glycol to the base glaze, conduct wet ultrafine grinding, wash and dry to obtain an antibacterial glaze prepared using zirconium silicate.
[0061] Comparative Example 1: Using Example 3 as the control group, replace erbium-doped zirconium silicate with zirconium silicate, and other processes are normal.
[0062] Comparative Example 2: Using Example 3 as the control group, replace silver-bismuth modified composite titanium dioxide with titanium dioxide, and other processes are normal.
[0063] Comparative Example 3: Using Example 3 as the control group, replace the composite dispersant with polyethylene glycol, and other processes are normal.
[0064] Comparative Example 4: Using Example 3 as the control group, replace the composite dispersant with modified acrylic acid, and other processes are normal.
[0065] Comparative Example 5: Using Example 3 as the control group, add a composite dispersant prepared by compounding 2.1% of modified acrylic acid and polyethylene glycol, and other processes are normal.
[0066] Comparative Example 6: Using Example 3 as the control group, add a composite dispersant prepared by compounding 2.9% of modified acrylic acid and polyethylene glycol, and other processes are normal.
[0067] Sources of raw materials used:
[0068] Zirconium oxychloride octahydrate 224316, erbium nitrate 298166, tetrabutyl titanate 244112, cerium nitrate 238538, bismuth nitrate 248592, silver nitrate 209139, zinc oxide 205532, barium carbonate 237108, polyethylene glycol 81269, acrylic acid 147230, itaconic acid I 29204, 2-acrylamido-2-methylpropanesulfonic acid 282731, sodium hypophosphite S5012: Merck reagent; potassium feldspar 68476-25-5: Hubei Chenghai Chemical Co., Ltd.; albite NIST99B: Sigma-Aldrich (Shanghai) Trading Co., Ltd.; silica powder 7440-21-3: Shanghai Xianxin New Material Technology Co., Ltd.; calcite (industrial grade): Hubei Kewode Chemical Co., Ltd.; dolomite T19847: Shanghai Yuanye Bio-Technology Co., Ltd.; wollastonite 13983-17-0: Hubei Qifei Pharmaceutical and Chemical Co., Ltd.; 809 frit: Shandong Zibo Jinming Glaze Co., Ltd.; ammonia water, sodium silicate, hydrochloric acid, ammonium fluoride, ethanol, sodium fluoride, sodium chloride, ammonium persulfate, sodium hydroxide, analytical pure: Reagents of Sinopharm Chemical Reagent Co., Ltd.
[0069] Performance test:
[0070] After applying the antibacterial glaze on the brick blank, sinter at 1000 °C to obtain a ceramic tile with a glaze thickness of 2 mm;
[0071] Antibacterial property: Cut the ceramic tile into test pieces of 18 mm × 8 mm, keep warm at 120 °C for 15 min, dilute the Escherichia coli bacterial liquid after cultivation by 1 / 20 times, adjust the concentration to 10 5 CFU / mL of bacterial suspension, drop 0.2 mL of the bacterial suspension on the test piece, keep warm at 35 °C for 18 h, then measure the number of surviving bacteria and calculate the antibacterial rate;
[0072] Antibacterial persistence: After standard scrubbing the test piece 1000 times with 6% sodium hypochlorite disinfectant solution, test the antibacterial property;
[0073] Refer to QB / T2761-2006 for formaldehyde removal rate test;
[0074] Refer to GB / T3810.7-2006 to test the wear resistance grade. Select 8.75 g of steel balls with a diameter of 1 mm as the grinding medium, test with a wear resistance tester, the sample size is 100 mm × 100 mm, test with 12000 revolutions, then refer to GB / T3810.14 for stain resistance test. Apply 3 drops of light oil medium green stain agent on the brick surface and keep it for 24 h. The light oil medium green stain agent uses light oil as the solvent, which contains 40% chromium green by mass fraction. The light oil is compounded by glycerol dicaprylate and glycerol tributyrate with a mass ratio of 1:1. Wash according to procedures A, B, C, and D to determine the stain resistance grade; the specific data is as follows in the table;
[0075]
[0076] The present invention provides a method for preparing an antibacterial glaze by utilizing zirconium silicate, wherein high-temperature-resistant rare earth ions are introduced into the glaze to enhance the antibacterial property of the glaze, so that the glaze still maintains a high antibacterial effect after high-temperature sintering, and by proportioning the glaze components and introducing a composite dispersant to perform wet ultrafine grinding when preparing the glaze, and by controlling the material ratio, a glaze surface formed by the prepared antibacterial glaze has the functions of self-cleaning and removing formaldehyde, thereby greatly improving the practicability of the antibacterial glaze and facilitating its market promotion.
[0077] Example 3 is compared with Comparative Example 1. The zirconium silicate in the present invention has excellent physical and chemical properties as an antibacterial glaze, such as high temperature resistance and strong acid and alkali corrosion resistance. However, large particles and serious agglomeration will affect its role as an antibacterial glaze. In the present invention, a nano-scale erbium-doped zirconium silicate with a narrow particle size distribution and no agglomeration is synthesized, thereby greatly improving its uniformity of dispersion in the antibacterial glaze.
[0078] Example 3 is compared with Comparative Example 2. Titanium dioxide, a photocatalytic antibacterial material with excellent broad-spectrum antibacterial efficacy, is introduced into the antibacterial glaze. However, the antibacterial property of pure titanium dioxide will be reduced when sintered at a temperature higher than 800°C. Therefore, a silver-bismuth modified composite titanium dioxide is synthesized in the present invention to enhance its high temperature resistance so that it still maintains excellent antibacterial properties after high-temperature sintering. Compared with titanium dioxide, the silver-bismuth modified composite titanium dioxide greatly improves its photodegradation efficiency after being contaminated by organic pollutants, thereby improving the self-cleaning performance of the glaze formed by the glaze.
[0079] Example 3 is compared with Comparative Examples 3, 4, 5 and 6. During wet ultrafine grinding, when 2.2-2.8% of a composite dispersant prepared by mixing modified acrylic acid and polyethylene glycol is added, the base glaze is ultrafinely ground to obtain particles with finer particle size and narrower particle size distribution. The composite dispersant produces more effective hydrogen bonds, making it easy to adsorb on the surface of the particles and wet them. During the grinding process, the rheological properties can be effectively improved, and stronger electrostatic repulsion potential and steric hindrance potential are generated between the particles, thereby facilitating the crushing of the particles and making their particle size tend to be consistent, so that the glaze surface formed after sintering is dense, thereby greatly improving its self-cleaning property.
[0080] The above descriptions are only embodiments of the present invention and are not intended to limit the patent scope of the present invention. All equivalent structural changes made using the present invention specification under the inventive concept of the present invention, or direct / indirect applications in other related technical fields, are included in the patent protection scope of the present invention.
Claims
1. A method for preparing an antibacterial glaze using zirconium silicate, characterized in that, It includes the following steps: S1: Mix erbium-doped zirconium silicate, silver-bismuth modified composite titanium dioxide, and a base glaze to obtain a base glaze. S2: Add a composite dispersant prepared by compounding modified acrylic acid and polyethylene glycol to the base glaze, conduct wet ultra-fine grinding, wash and dry it to obtain an antibacterial glaze prepared using zirconium silicate.
2. The method for preparing an antibacterial glaze using zirconium silicate according to claim 1, characterized in that, By mass fraction, the composition of the base glaze is: 10 - 20% erbium-doped zirconium silicate, 8 - 16% silver-bismuth modified composite titanium dioxide, and the balance is the base glaze.
3. The method for preparing an antibacterial glaze using zirconium silicate according to claim 1, characterized in that, By mass parts, the composition of the base glaze is: 19 - 20 parts of potassium feldspar, 5 - 6 parts of sodium feldspar, 31 - 33 parts of silica powder, 2 - 4 parts of zinc oxide, 3 - 6 parts of calcite, 3 - 5 parts of dolomite, 15 - 17 parts of wollastonite, 2 - 3 parts of barium carbonate, and 3 - 5 parts of 809 frit.
4. The method for preparing an antibacterial glaze using zirconium silicate according to claim 1, characterized in that, The working conditions for wet ultra-fine grinding are: Grind using a medium stirring mill. The rotational speed of the main shaft of the medium stirring mill is 2000 rpm. The grinding medium used is yttrium-stabilized zirconia beads with a bead diameter of 0.2 - 0.3 mm. The volume filling rate of the grinding beads is 78 vol.%, the pH is 6.8 - 7.2, and the grinding time is 80 - 100 min.
5. The method for preparing an antibacterial glaze using zirconium silicate according to claim 1, characterized in that, The mass ratio of modified acrylic acid to polyethylene glycol in the composite dispersant is 1:
10.
6. The method for preparing an antibacterial glaze using zirconium silicate according to claim 1, characterized in that, The mass ratio of the composite dispersant to the base glaze is 2.2 - 2.8%.
7. The method for preparing an antibacterial glaze using zirconium silicate according to claim 1, characterized in that, The preparation of modified acrylic acid includes the following steps: Mix acrylic acid, itaconic acid, 2-acrylamido-2-methylpropanesulfonic acid, sodium hypophosphite, and deionized water, heat up to 65 - 70 °C, under nitrogen protection, add an aqueous solution of ammonium persulfate, heat up to 75 - 80 °C, and then adjust the pH to 7 - 8 with sodium hydroxide to obtain modified acrylic acid.
8. The method for preparing an antibacterial glaze using zirconium silicate according to claim 1, characterized in that, The preparation of erbium-doped zirconium silicate includes the following steps: Mix zirconium oxychloride octahydrate and deionized water, add erbium nitrate, and adjust the pH to 2.8 - 3.2 with ammonia water, denoted as solution A; mix sodium silicate and deionized water, and adjust the pH to 2.8 - 3.2 with hydrochloric acid, denoted as solution B; under stirring conditions, add solution A and solution B together to an ammonium fluoride solution, adjust the pH to 2.8 - 3.2 with hydrochloric acid, keep it in a water bath at 75 - 80 °C for 5 - 6 h, cool and age for 10 - 12 h, filter and wash with deionized water and ethanol 3 - 5 times, dry, add sodium fluoride and sodium chloride, mix and pass through a 200-mesh sieve, keep it at 900 °C for 2 h, cool and grind, and conduct pickling, washing, and drying in sequence to obtain erbium-doped zirconium silicate.
9. The method for preparing an antibacterial glaze using zirconium silicate according to claim 1, characterized in that, The preparation of silver-bismuth modified composite titanium dioxide includes the following steps: Mix anhydrous ethanol and tetrabutyl titanate, add a mixed solution of deionized water, anhydrous ethanol, and cerium nitrate, then add bismuth nitrate and silver nitrate in sequence, transfer it to a reaction kettle and keep it at 105 - 110 °C for 46 - 48 h, centrifuge and wash with anhydrous ethanol and deionized water 3 - 5 times in sequence, dry, heat up to 200 °C at a rate of 15 °C / min in an argon atmosphere and keep it for 1 h, then heat up to 450 °C at the same speed and keep it for 2 h to obtain silver-bismuth modified composite titanium dioxide.
10. The method for preparing an antibacterial glaze using zirconium silicate according to claim 9, characterized in that, The mass ratio of bismuth nitrate, silver nitrate, and cerium nitrate is 0.1:0.1:0.29.
Citation Information
Cited By
High-glossiness and high-whiteness ceramic glaze and preparation method thereof
CN122079489A
Ceramic glaze with high gloss and high whiteness and preparation method thereof
CN122079489B
